The initial impact of No Child Left Behind with a focus on time for elementary science and equity in science, math, and reading - Griffith, George W. (Kansas State University, 2009)
This research examines the impact of the “No Child Left Behind” (NCLB) Act on elementary science education in the states of Colorado, Kansas, Missouri, Nebraska, and Oklahoma. Elementary teachers (n=928 total for all states) responded to an online survey, which included both closed-ended and open-ended questions pertaining to the time spent on science instruction and any changes made in science instruction since the implementation of NCLB. More than half of these teachers indicated they have cut time from science instruction since NCLB became law. Follow-up questions with regard to why changes were made in science instruction were also included in the survey. The need to increase time for math and reading instruction was a belief expressed by many of the respondents with other respondents stating a member of their administration mandated changes. This research also examines results from the National Assessment of Educational Progress (NAEP) for each of these states to determine if the changes made in response to NCLB helped meet the goal of closing the achievement gap between the disaggregated subgroups of gender, race, and socioeconomic status (SES). The data from the NAEP shows only a few significant changes occurred; however, some included a significant increase in the achievement gap.
Keywords: NCLB; Equity; Change; Assessment; Education; Science; Education, Administration (0514); Education, Curriculum and Instruction (0727); Education, Philosophy of (0998)